A The Attitude and Social Behavior in The Implementation of Student Character Education in Madrasah Aliyah Al Asror - irawan, gejek slamet; Suyahmo, Suyahmo; Utomo, Cahyo Budi (Universitas Negeri Semarang, 2021)
The purpose of this study is to determine the implementation of student character education in Madrasah Aliyah Al Asror, to find out how the implementation of student character education in Madrasah Aliyah Al Asror in shaping the attitudes and behavior in the community. The research approach used was qualitative phenomenology. Data were collected by interviewing informants consisting of the head of the madrasah, the teachers, and the community leaders, observing the madrasah environment and studying the documents. The data validity techniques were validity, triangulation. The data analysis techniques used were data collection, data reduction, data presentation, and drawing conclusion. The results showed that character education in MA Al Asror based on the results of research conducted inside and outside the classroom such as before teaching and learning activities the students were accustomed to praying, then the teacher gave motivation to students, in the middle of delivering the material the teacher delivered social values and at the end of the lesson the teacher gave assignments to students. The conclution of this research is, the students are expected to be able to have religious character, respect, and responsible during the activities inside and outside the classroom.